Legal Analysis of the Role of Notaries in the Process of Risk-Based Licensing Digitalization Through Oss-Rba - Ritza Aurelia, Tsabita; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze: 1). The role of notaries in the process of digitalizing risk-based licensing through OSS-RBA. 2) Obstacles and solutions in the process of digitalizing risk-based licensing through OSS-RBA. This type of research is empirical legal research. The approach method in this study is a sociological juridical approach. The types of data in this study are primary data and secondary data. The data collection method uses interviews and literature studies. The analysis in this study is qualitative. The results of the study concluded: 1) The role of notaries in the process of digitalizing risk-based licensing through OSS-RBA is as a guarantor of the certainty and validity of legal documents that form the basis for establishing a business entity as well as the main requirement in obtaining a Business Identification Number (NIB) and other permits. Although the OSS-RBA system is present as a digital instrument that simplifies and accelerates business licensing services, the function of notaries remains irreplaceable because their attributive authority is sourced from the Notary Law (UUJN) to make authentic deeds. In Sukoharjo Regency, which is dominated by MSMEs, notaries also act as a bridge between legal literacy and digital administration, assisting business actors in understanding, preparing, and ensuring the validity of documents required in the OSS-RBA system. 2) Obstacles in the process of digitizing risk-based licensing through OSS-RBA are not only technical, such as limited technological infrastructure and low digital literacy among business actors, but also normative, namely unclear procedures, overlapping regulations, and too rapid policy changes that create legal uncertainty. Possible solutions include improving coordination between agencies, drafting more consistent regulations, technical assistance for business actors, and the role of notaries in guaranteeing the validity of legal documents and maintaining data accuracy in the OSS-RBA system. When analyzed using Gustav Radbruch's theory of legal certainty, OSS-RBA-based licensing should be able to ensure that the law is clear, consistent, and can be implemented without causing doubt. According to Radbruch, legal certainty is one of the fundamental values of law besides justice and utility. Legal certainty can only be realized if implementing regulations are stable, administrative procedures are integrated, and mechanisms for resolving obstacles can be implemented effectively.